A necessidade da instauração do incidente de desconsideração da personalidade jurídica no redirecionamento de execuções fiscais. Entendimento das turmas do STJ - ARAÚJO, Márcia Caroline Santos (2024)
This article seeks to relate the compatibility of Law No. 13,105/2015 with the Tax Enforcement Law (LEF). First, it will examine how the CPC/2015 applies subsidiarily to tax enforcement. Next, there will be an analysis of the specific aspects of the IDPJ, highlighting its characteristics and purposes. One of the central points will be the identification of possible antinomies between the IDPJ and the LEF, considering the objectives of both regulations. Finally, the article will propose a unified interpretation of the legal system that promotes a harmonious integration between the provisions of the Code and the guidelines of the LEF. This approach aims not only to clarify existing doubts but also to contribute to a more effective and coherent application of the norms in the context of tax enforcement.